Dialektika Islam Dengan Varian Kultur Lokal Dalam Pola Keberagamaan Masyarakat Sasak - Kamarudin Zaelani (Ulumuna, 2005)
Lombok Island known as the one-thousand-mosque island not only provides a great number of legends about its existential background but also historical facts and artifacts that legitimate the identity of this virgin island. They inspired and motivated every educated Sasakness—appellation to indigenous of Lombok people—to make intensive research on the subjects. Such the activity has a great benefit in term of identifying and perpetuating good cultural heritages of the people in the past, and then implementing them in the current context. This is the meaning addressed by the Islamic jurisprudence principle “al-muhâfadzah ‘alâ al-qadîm al-shâlih wa al-akhdz bi al-jadîd al-ashlah”. This article is aimed at revealing historical root of religious identity of Sasak community. Historical sketch of its religious identity leads to Wetu Telu religion that was the collaboration of tradition, cultural, and religious values of the comers and those of the indigenous people in the past. Another point of view said that Wetu Telu religion is an uncompleted process of islamization toward Waktu Lima religion that is considered by presently most Muslims in Lombok the true and pure Islam.